TiO2/ diazonium/graphene oxide composites: synthesis and visible-light driven photocatalytic degradation of methylene blue - Hoan Thi Vuong Nguyen (TGC); Minh Ngoc Nguyen; Thoi Thi Kim Nhi; Nguyen Van Thang; Tuan Anh Vu; Vo Thang Nguyen; Nguyen Mau Thanh; Nguyen Van Hung; Dinh Quang Khieu (My University, 2020)
TiO2/ diazonium/graphene oxide composites: synthesis and visible-light driven photocatalytic degradation of methylene blue
Keywords: TiO2/Diazonium